SISTEM KONTROL INFORMASI AKTIVITAS LANSIA BERBASIS INTERNET OF THINGS (IoT) - Pujianti Wahyuningsih (ILKOM Jurnal Ilmiah, 2018)
Elderly is a human phase are notabel to much do an activity because of physical factors and age. On doing daily activity the elderly should be kept by the family or nurse so in this research will be built a control system thatabel to detection of elderly activity and control an electronic device remotely using the Internet of Things (IoT). All of the elderly activity has detected based on sensor data input from the carpet, PIR sensor, DHT22 temperature sensor then processed in the Arduino Mega and Raspberry Pi. The function of Raspberry Pi is to connect all elderly information to the internet using node.js. Based on the information the family or nurse able to see the elderly activity remotely using website and able to control electronic device like a fan and heater by manually and automatically using the Internet of Things technology.